Insulin negatively regulates dedifferentiation of mouse adipocytes in vitro - Liguo Zang (2020)
© 2020, © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group. Insulin plays an important role during adipogenic differentiation of animal preadipocytes and the maintenance of mature phenotypes. However, its role and mechanism in dedifferentiation of adipocyte remains unclear. This study investigated the effects of insulin on dedifferentiation of mice adipocytes, and the potential mechanisms. The preadipocytes were isolated from the subcutaneous white adipose tissue of wild type (WT), TNFα gene mutant (TNFα-/-), leptin gene spontaneous point mutant (db/db) and TNFα-/-/db/db mice and were then induced for differentiation. Interestingly, dedifferentiation of these adipocytes occurred once removing exogenous insulin from the adipogenic medium. As characteristics of dedifferentiation of the adipocytes, downregulation of adipogenic markers, upregulation of stemness markers and loss of intracellular lipids were observed from the four genotypes. Notably, dedifferentiation was occurring earlier if the insulin signal was blocked. These dedifferentiated cells regained the potentials of the stem cell-like characteristics. There is no significant difference in the characteristics of the dedifferentiation between the adipocytes. Overall, the study provided evidence that insulin plays a negative regulatory role in the dedifferentiation of adipocytes. We also confirmed that both dedifferentiation of mouse adipocytes, and effect of the insulin on this process were independent of the cell genotypes, while it is a widespread phenomenon in the adipocytes.